Cleavage of the Meckel-Gruber syndrome protein TMEM67 by ADAMTS9 uncouples Wnt signaling and ciliogenesis - Manu Ahmed; Sydney Fischer; Karyn L. Robert; Karen I. Lange; Michael W. Stuck; Sunayna Best; Colin A. Johnson; Gregory J. Pazour; Oliver E. Blacque; Sumeda Nandadasa (Nature Communications)
Abstract TMEM67 mutations cause Meckel-Gruber syndrome and other related ciliopathies. TMEM67 is involved in both ciliary transition zone assembly, and non-canonical Wnt signaling mediated by its extracellular domain. How TMEM67 performs these two separate functions is not known. We identify a cleavage motif in the extracellular domain of TMEM67 cleaved by the extracellular matrix metalloproteinase ADAMTS9. This cleavage regulates the abundance of two functional forms: a C-terminal portion which localizes to the ciliary transition zone regulating ciliogenesis, and a non-cleaved form which regulates Wnt signaling. By characterizing three TMEM67 ciliopathy patient variants within the cleavage motif utilizing mammalian cell culture and C. elegans, we show the cleavage motif is essential for cilia structure and function, highlighting its clinical significance. We generated a non-cleavable TMEM67 mouse model which develop severe ciliopathies phenocopying Tmem67 -/- mice, but in contrast, transduces normal Wnt signaling, substantiating the existence of two functional forms of TMEM67.